Employee playfulness: effects of personality and organisational climate. (17th March 2021) - Ho, Yu-Ling; Chen, Ching-Yueh; Lin, Liang-Hung
Many studies have suggested the importance of playfulness at workplace and that playfulness is likely to be affected by employees' own personality as well as the work environment. In the era of uncertainty, 'employees' or 'talents' are the key for organisations to remain competitive in the industry. This study therefore aims to find out the antecedents-personality traits and organisational playfulness climate-in employee playfulness. Grounded on the analysis of survey, this study finds that big five personality traits, in particular extraversion and openness to experience, are positively associated with employees' personal playfulness. Moreover, organisational playfulness climate, in particular an organisational climate characterised by playing together and pressure release, has a positive impact on employees' personal playfulness at workplace.